An ecological and neurobiological perspective on the evolution of vocal learning - Brenowitz, Eliot A.; Beecher, Michael D. (Frontiers in Ecology and Evolution, 2023)
Vocal learning is a distinctive phenomenon, inherently interesting to humans given our unique proficiency with language (Hauser et al., 2002;Beecher, 2021). Other than humans, the ability to learn to produce species-typical vocalizations has been demonstrated definitively only in three avian taxa (oscine passerines or songbirds, parrots and hummingbirds), and four mammalian taxa (cetaceans, pinnipeds, bats and elephants). In most taxa that use acoustic communication, animals develop signals normally without environmental input such as hearing the vocal signals of conspecific adults. We refer to such signals, and their underlying developmental program, as "innate."There is an extensive literature on the evolution of vocal learning in humans and animals, which attempts to explain why it has evolved so rarely, and examining whether there are evolutionary antecedents to vocal learning in nonhuman primates and other mammalian taxa. Most of this literature focuses on what qualifies as vocal learning (e.g.